2002
DOI: 10.1002/jez.10095
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sex determination in the European sea bass, Dicentrarchus labrax (L., 1758) (Teleostei, Perciformes, Moronidae): Critical sensitive ontogenetic phase

Abstract: The temperature sex determination (TSD) mechanism in the European sea bass (Dicentrarchus labrax L.) was studied in respect to: a) the TSD sensitivity during the different developmental stages; and b) the intrapopulation correlation of sex determination with the growth rate up to the end of the TSD-sensitive period. At the stage of half-epiboly, eggs from the same batch were divided into four groups and subjected to different thermal treatments: a) 15 degrees C (G15 group) and b) 20 degrees C (G20 group) up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 39 publications
5
70
1
6
Order By: Relevance
“…Besides swimming performance, it has been shown to affect growth, metabolism, time of hatching (Herzig and Winkler 1986), development (Herzig and Winkler 1986;Fukuhara 1990;Polo et al 1991;Gibson and Johnston 1995;Lein et al 1997), yolk absorption (Fukuhara 1990), muscle ontogeny and development (Johnston 1981(Johnston , 1993ontogeny of internal organs (Fukuhara 1990;Gibson and Johnston 1995), external morphology (Lindsey 1988;Wimberger 1992;Tudela 1999;Koumoundouros et al 2001a;Pakkasmaa and Piironen 2001;Cabral et al 2003;Silva 2003;Turan 2004), meristic characters (Turan 2004), appearance of skeletal deformities (Polo et al 1991;Koumoundouros et al 2001b), sex determination (Baroiller et al 1999;Pavlidis et al 2000;Koumoundouros et al 2002a) and the overall survival (Fukuhara 1990;Lein et al 1997) and lifespan of fish (Malek et al 2004). Although the effect of swimming temperature on the performance of fish has been studied thoroughly and in a wide range of species, there are only a few studies focusing on the impact of rearing temperature on the swimming performance of adult fish (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Besides swimming performance, it has been shown to affect growth, metabolism, time of hatching (Herzig and Winkler 1986), development (Herzig and Winkler 1986;Fukuhara 1990;Polo et al 1991;Gibson and Johnston 1995;Lein et al 1997), yolk absorption (Fukuhara 1990), muscle ontogeny and development (Johnston 1981(Johnston , 1993ontogeny of internal organs (Fukuhara 1990;Gibson and Johnston 1995), external morphology (Lindsey 1988;Wimberger 1992;Tudela 1999;Koumoundouros et al 2001a;Pakkasmaa and Piironen 2001;Cabral et al 2003;Silva 2003;Turan 2004), meristic characters (Turan 2004), appearance of skeletal deformities (Polo et al 1991;Koumoundouros et al 2001b), sex determination (Baroiller et al 1999;Pavlidis et al 2000;Koumoundouros et al 2002a) and the overall survival (Fukuhara 1990;Lein et al 1997) and lifespan of fish (Malek et al 2004). Although the effect of swimming temperature on the performance of fish has been studied thoroughly and in a wide range of species, there are only a few studies focusing on the impact of rearing temperature on the swimming performance of adult fish (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the percentage of females declines with increasing temperature (Table 2.1), although in one genus of flatfishes (Paralichthys) the percentage of females is maximal at intermediate temperatures, and in another species (Dicentrarchus labrax) different investigators have reported opposite results (Pavlidis et al 2000;Koumoundouros et al 2002;Blázquez et al 1998b;Saillant et al 2002). In Oreochromis niloticus, XX genotypes tend to be masculinized by high temperature, while YY genotypes tend to be feminized (Abucay et al 1999;Kwon et al 2002).…”
Section: Tsd and Other Thermal Sex Ratio Distortions In Fishesmentioning
confidence: 99%
“…Distinct thermosensitive periods (TSPs) of sex determination have been identified in several species including various atherinids (Conover and Fleisher 1986;Strüssmann et al 1996aStrüssmann et al , 1997, European sea bass (Koumoundouros et al 2002), flatfish (Yamamoto 1999), and tilapia (reviewed in Baroiller and D'Cotta 2001). Frequently, the TSP precedes and/or coincides with the end of the larval period and occurs prior to the onset of histological gonad differentiation.…”
Section: Tsd and Other Thermal Sex Ratio Distortions In Fishesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different environmental parameters, water temperature is most vital. The impact of temperature on fish ontogeny affecting the growth and development rates (Batty et al, 1986;Polo et al, 1991), mortality (Watanabe et al, 1995), deformities (Bolla and Holmefjord, 1988), size at feeding onset, notochord flexion or metamorphosis (Polo et al, 1991;Overnell, 1997;Fuiman et al, 1998), stage duration (Camus and Koutsikopoulos, 1984;Koumoundouros et al, 2001), muscle ontogeny (Stickland et al, 1988;Galloway et al, 1999), sex determination (Conover and Kynard, 1981;Baroiller et al, 1999;Koumoundouros et al, 2002), hatching (Rana, 1990), survival rates (Marangos et al, 1986;Polo et al, 1991), total length at feeding onset (Polo et al, 1991;Koumoundouros et al, 2001) and efficiency of yolk utilisation (Polo et al, 1991) have been used as the criteria for estimation of optimum temperatures for fish larvae.…”
mentioning
confidence: 99%